Running the Risk of an Injury in the NFL: Short-Run and Career Consequences - Quinn Keefer; Thomas J. Kniesner (Institute of Labor Economics (IZA), 2019)
Similar to other workers in industrial settings NFL running backs can choose to provide additional work effort with possible negative health consequences. We find that the most informative measure for running backs is yards gained after contact, which not only increases total rushing yards but also increases injuries that can cause subsequent lost income due to future games missed. We econometrically examine the decisions running backs reveal in trading off injury risk against total yards gained and salary in the short run and how the tradeoff appears in the longer run where career length considerations come into play. Our estimates reveal subtle nonlinearities and interpersonal heterogeneity in risky effort and the associated short and long run injury risk and economic payoffs.
Keywords: Z21; Z22; C23; 330; non-fatal injuries; NFL; running backs; risky effort; rate-of-return; career length; Poisson regression; Arellano-Bond model; panel data; fixed effects